Unraveling the Effects: Broad-spectrum Antibiotics, Gut Microbiota Disruption, and Gastrointestinal Health - Wagh, Snehal; Marulkar, Chaitrali S (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The modern lifestyle is not complete without antibiotics. By curing and preventing illness, as well as increasing feed efficiency for farm animals, they enhance our quality of life. Antibiotic use does not, however, come without side effects. Despite their importance in treating a variety of bacterial diseases, broad-spectrum antibiotics can have unexpected effects on gut microbiota due to their indiscriminate nature. This review looks at the major effects of broad-spectrum antibiotics on the gut flora and the side effects that may result. Antibiotics cause a disturbance in the delicate equilibrium of gut microbial populations, resulting in a reduction in microbial diversity and an increase in pathogenic organisms. Many gastrointestinal problems, such as dysbiosis, diarrhea, and more serious illnesses like antibiotic-associated colitis, can be brought on by these changes. We investigate the ways in which antibiotics cause microbial imbalances, such as the inhibition of helpful bacteria and the encouragement of the expansion of harmful bacteria. We also look at the long-term effects of these changes on gut health and their clinical implications. This review aims to provide a comprehensive overview of how broad-spectrum antibiotics influence gut health and to inform future research directions in microbiome management and therapeutic interventions.